Lampungnese Politeness Strategy - Redika Cindra Reranta (TEKNOSASTIK, 2023)
The study of politeness strategy in various cultures needs to be explored more since contact among the communities cannot be avoided today while each culture has its standard of the point. Thus, analyses of the discussion are urgently important to be conducted to present theories of politeness so then people can understand, adapt or apply others' strategies when the context is changed to avoid conflict; misinterpretation, and culture shock between speakers. For this reason, this research analyzed the politeness strategy of Lampungnese, a local ethnicity in Lampung province, a transmigrated target area that has multiple ethnicities whom they contact. Next, the data of this research were a recording of natural communication collected by direct observation in the community and a list of Lampungnese values of politeness obtained by interviews with Lampungnese scholars and culturalists. Having abundant data, a comprehensive analysis was qualitatively done by the researcher in order to answer the research question, what are Lampungnese politeness strategies? Finally, it was reached seven strategies based on the result of the analysis. In accordance, five of them are common strategies as Leech (2014) proposed in his theory, while the rest are local strategies that are possibly not found in other ethnicities.